汪曾祺与林语堂饮食散文的比较研究 - 寇, 泽玉 (2023)
林语堂与汪曾祺是中国现当代文学史上两位具有代表性的闲适作家，二者文学 创作中都分布有数量、质量相当可观的饮食类散文。本论文以林语堂与汪曾祺的饮 食散文为研究对象，从创作题材、艺术笔调、文化意蕴、饮食散文异同原因四方面 对二者的饮食散文进行比较探讨。 第一章绪论部分通过对研究缘起、饮食散文及林语堂、汪曾祺散文的研究现 状、研究方法等方面的介绍，阐明了林语堂与汪曾祺饮食散文比较研究的空缺与本 论文选题的可行性。 第二章从林语堂与汪曾祺饮食散文的创作题材着手，用“过去记忆重建理论” 解释了他们通过故乡及旅居地的饮食书写重返旧日时光的文学现象。分析了二人借 饮食表达的不同人生哲思。 第三章从两者饮食散文的艺术笔调出发，论述了汪曾祺传承林语堂“性灵”、 “闲适”观的具体表现。语言风格上二人各有千秋，林语堂的语言夸张通俗，汪曾 祺行文朴素平淡。 第四章对两者饮食散文的文化意蕴进行了分析比较。严谨的知识考据丰富了他 们饮食散文的文化内涵。林语堂对中西饮食文化进行了对比及思索，汪曾祺则着重 发掘中国民间文化蕴涵的人文、历史精神。 第五章结合两位作家的家庭背景及求学经历，探析了二人饮食散文书写异同的 原因。 第六章是结语部分，对本论文进行了回顾和简要总结。As two representative leisure writers in the history of modern and contemporary Chinese literature, Lin Yutang and Wang Zengqi created a considerable quantity and quality of dietary prose in their literary works. This paper takes Lin Yutang and Wang Zengqi's dietary prose as the research object to compares and discusses the two dietary prose from four aspects, which are creative theme, artistic style, cultural implication, and the reasons for the similarities and differences of dietary prose. The first chapter, the introduction, clarifies the status that there exists a gap in the comparative study of Lin Yutang and Wang Zengqi's dietary prose, also emphasize the feasibility of this thesis by introducing the followings: the background of the study, the dietary prose, the research status and research methods of Lin Yutang and Wang Zengqi's prose. The second chapter uses "theory of reconstruction of past memory" to explain the literary phenomenon of returning to the old days through the description of the diet writing about their hometown and sojourn from the point where creation themes of Lin Yutang and Wang Zengqi's prose on diet starts, as well as analyzes the different philosophies of life expressed by the two through their diet. The third chapter discusses the concrete expression of Wang Zengqi's inheritance of Lin Yutang's "spiritual" and "leisure" views from the artistic style of the two dietary prose. In terms of language style, the two have their own strengths and weaknesses respectively. Lin Yutang's language is exaggerated and popular, while Wang Zengqi's prose is simple and plain. The fourth chapter analyzes and compares the cultural connotations of the two dietary prose. Rigorous knowledge research has enriched the cultural connotation of their dietary prose. Lin Yutang made a comparison and reflection on Chinese and Western food culture, while Wang Zengqi focused on exploring the humanistic and historical spirit contained in Chinese folk culture. The fifth chapter analyzes the reasons for the similarities and differences of the two writers' dietary prose writing based on their family background and study experience of the two writers. The sixth chapter is the conclusion part, which reviews and briefly summarizes the thesis.